FK Student Best Paper Award - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 5 July 2021 - Congratulations! Md. Saef Ullah Miah, FK postgraduate student and his supervisor Senior Lecturer FK, Dr. Junaida Sulaiman, have won the best paper award in the International Conference of Intelligent Computing and Informatics (ICOICS 2021).